Characterization of Geochemistry in Hydrothermal Sediments From the Newly Discovered Onnuri Vent Field in the Middle Region of the Central Indian Ridge - Lim, Dhongil; Kim, Jihun; Kim, Wonnyon; Kim, Jonguk; Kim, Dongsung; Zhang, Le; Kwack, Kyungun; Xu, Zhaokai (Frontiers in Marine Science, 2022)
The recently discovered Onnuri hydrothermal vent field (OVF) is a typical off-axis ultramafic-hosted vent system, located on the summit of the dome-like ocean core complex (OCC) at a distance of ~12 km from the ridge axis along the middle region of the Central Indian Ridge (CIR). The plume chemistry with high methane anomaly was consistent with the precursor of hydrothermal activity; however, the fundamental characteristic of the OVF system, such as the hydrothermal circulation process and source of heat, remains poorly understood. Here, we focus on the geochemical features of surface sediments and minerals collected at and around the OVF region in order to better understand this venting system. The results reveal that the OVF sediments are typified by remarkably high concentrations of Fe, Si, Ba, Cu, and Zn, derived from hydrothermal fluid and S and Mg from seawater; depleted C-S isotope compositions; and abundant hydrothermally-precipitated minerals (i.e., Fe-Mn hydroxides, sulfide and sulfate minerals, and opal silica). Notably, the occurrence of pure talc and barite bears witness to strong hydrothermal activity in the OVF, and their sulfur and strontium isotope geochemistry agree with extensive mixing of the high-temperature hydrothermal fluid derived from the ultramafic mantle rocks with unmodified seawater. The findings reveal that the OVF is a representative example of an off-axis, high-temperature hydrothermal circulation system, possibly driven by the exothermic serpentinization of exposed peridotites. Given the widespread distribution of OCC with detachment faults, furthermore, the OVF may be the most common type of hydrothermal activity in the CIR, although the paucity of data precludes generalizing this result. This study provides important information contributing to our understanding of the ultramafic-hosted hydrothermal vent systems with a non-magmatic heat source along mid-ocean ridges.